Answer:
![f(x)=-2x(x+4)](https://tex.z-dn.net/?f=f%28x%29%3D-2x%28x%2B4%29)
Step-by-step explanation:
We want to find the equation of a quadratic function in factored form with zeros at <em>x</em> = -4 and <em>x</em> = 0 that passes through the point (-3, 6).
The factored form of a quadratic is given by:
![f(x)=a(x-p)(x-q)](https://tex.z-dn.net/?f=f%28x%29%3Da%28x-p%29%28x-q%29)
Where <em>p</em> and <em>q</em> are the zeros and <em>a</em> is the leading coefficient.
Since we have zeros at <em>x</em> = -4 and <em>x</em> = 0, let <em>p</em> = -4 and <em>q</em> = 0. Substitute:
![f(x)=a(x-(-4))(x-0)](https://tex.z-dn.net/?f=f%28x%29%3Da%28x-%28-4%29%29%28x-0%29)
Simplify:
![f(x)=ax(x+4)](https://tex.z-dn.net/?f=f%28x%29%3Dax%28x%2B4%29)
And since we know that the function passes through the point (-3, 6), f(x) = 6 when <em>x</em> = -3. Thus:
![(6)=a(-3)(-3+4)](https://tex.z-dn.net/?f=%286%29%3Da%28-3%29%28-3%2B4%29)
Simplify:
![6=a(-3)(1)](https://tex.z-dn.net/?f=6%3Da%28-3%29%281%29)
Thus:
![-3a=6\Rightarrow a=-2](https://tex.z-dn.net/?f=-3a%3D6%5CRightarrow%20a%3D-2)
So, our quadratic function is:
![f(x)=-2x(x+4)](https://tex.z-dn.net/?f=f%28x%29%3D-2x%28x%2B4%29)
Answer:
-2
Step-by-step explanation:
Between the first two steps we see ...
![15(x-\boxed{^})=25\\\\15x+30=25](https://tex.z-dn.net/?f=15%28x-%5Cboxed%7B%5E%7D%29%3D25%5C%5C%5C%5C15x%2B30%3D25)
Applying the distributive property to the first equation and comparing to the second, we see that ...
![-15\boxed{^}=30\\\\\boxed{^}=\dfrac{30}{-15}=-2](https://tex.z-dn.net/?f=-15%5Cboxed%7B%5E%7D%3D30%5C%5C%5C%5C%5Cboxed%7B%5E%7D%3D%5Cdfrac%7B30%7D%7B-15%7D%3D-2)
The number in the box should be -2.
The standard form of equation is: 4x+2y = -13
Step-by-step explanation:
the standard form of a linear equation in two variables is given by:
![ax+by = c](https://tex.z-dn.net/?f=ax%2Bby%20%3D%20c)
Given equation is:
![2y+5=-4(x+2)](https://tex.z-dn.net/?f=2y%2B5%3D-4%28x%2B2%29)
Distributing -4 into the round bracket
![2y+5 = -4x-8](https://tex.z-dn.net/?f=2y%2B5%20%3D%20-4x-8)
Adding 4x on both sides
![4x+2y+5 = -4x-8+4x\\4x+2y+5 = -8](https://tex.z-dn.net/?f=4x%2B2y%2B5%20%3D%20-4x-8%2B4x%5C%5C4x%2B2y%2B5%20%3D%20-8)
subtracting 5 from both sides
![4x+2y+5-5 = -8-5\\4x+2y = -13](https://tex.z-dn.net/?f=4x%2B2y%2B5-5%20%3D%20-8-5%5C%5C4x%2B2y%20%3D%20-13)
The standard form of equation is: 4x+2y = -13
Keywords: Linear equation, variables
Learn more about linear equations at:
#LearnwithBrainly
Answer:
f = 5.12
Step-by-step explanation:
f(8)=0.8(8)^2
f(8)=6.4^2
f(8)=40.96
f(8)/8 = 40.96/8
f = 5.12
i'd really appreciate being marked brainliest if you want! i appreciate it :)
Answer:
4/10 is the answer
Step-by-step explanation:
brainliest plss